Implementasi Sistem Among melalui Model Pembelajaran PBL pada Pendidikan Pancasila Kelas X PM 3 - Ainul Siti Fatimah; Supriyono Purwosaputro; Puput Tri Hartanti (Journal on Education, 2024)
This research aims to describe the implementation of the among system KHD through the Problem Based Learning learning model in Pancasila Education subjects. This research will be carried out in Class X PM 3 SMK Negeri 2 Semarang with the material "Identifying Individual Identity and Group Identity". In this research, the researcher will describe in descriptive form the implementation of the Among System through the PBL Learning Model in the Pancasila Education Subject Class X PM 3 SMK N 2 Semarang. Data obtained through direct observation during the learning process, and also reflections filled in by students. The research results show that the among system has been implemented in the learning process. This implementation was carried out by collaborating with the among system and the Problem Based Learning learning model. From the research day, it can be understood that teachers have an important role in education, not only limited to teaching or providing material, but teachers are also guides, mediators, facilitators, evaluators, providing examples, providing direction, encouragement or motivation to students.